Perceived organizational support as a moderator of affective well-being and occupational stress - Sadia Malik; Saima Noreen (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
The present study aimed to find out the Perceived Organizational Support as a moderator of relationship between occupational stress and affective well-being among teachers. A sample of (N=210) was drawn from schools, colleges and University teachers including both male and female teachers. Purposive sampling technique was used having a specific age range, education, marital status, nature of institute and job experience. Survey research design was used. To collect data job related affective wellbeing scale (Van Katwyk, Fox, Spector and Kelloway, 2000), perceived organizational scale (Rhoades and Eisenberger, 2002) and occupational stress scales (French & Caplan, 1972) were individually administered. The results suggested relationship between occupational stress, perceived and well-being among teachers. Perceived organizational support works as a moderator for well-being and occupational stress of teachers. Suggestions for the future researches and implications have been discussed.
Keywords: 330; perceived organizational support; affective well-being; occupational stress